2007
DOI: 10.1016/j.immuni.2007.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating γδ T Cells Suppress T and Dendritic Cell Function via Mechanisms Controlled by a Unique Toll-like Receptor Signaling Pathway

Abstract: gammadelta T cells are important contributors to innate immunity against cancer, but their regulatory role in controlling immune responses remains largely unknown. Here we report that a dominant gammadelta1 T cell population among lymphocytes infiltrating breast tumors possessed a potent ability to suppress naive and effector T cell responses and to block the maturation and function of dendritic cells. Adoptive cotransfer experiments demonstrated their in vivo suppressive activity. However, their immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
450
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(475 citation statements)
references
References 47 publications
15
450
1
Order By: Relevance
“…Therefore, these findings provide clear evidence that gd T cells would represent a dominant IL-17-producing lymphocyte subset during physiological tumor development. Consistently, previous papers demonstrated that a substantial number of gd T cells were observed in human breast, prostate, and renal cancer tissues [39]. As we confirmed that human gd T cells differentiated into IL-17-producing cells, at least in the presence of IL-6, TGF-b and IL-23 (data not shown), IL-17 might be produced by gd T cells in these types of cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, these findings provide clear evidence that gd T cells would represent a dominant IL-17-producing lymphocyte subset during physiological tumor development. Consistently, previous papers demonstrated that a substantial number of gd T cells were observed in human breast, prostate, and renal cancer tissues [39]. As we confirmed that human gd T cells differentiated into IL-17-producing cells, at least in the presence of IL-6, TGF-b and IL-23 (data not shown), IL-17 might be produced by gd T cells in these types of cancer.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, we demonstrated the presence of antigenspecific CD4 þ Treg cells at tumor sites (Wang et al, 2004, and showed that Treg cells suppressed the proliferation of naive CD4 þ T cells and inhibited IL-2 secretion of CD4 þ effector cells upon activation by tumor-specific antigens . Finally, we recently identified CD8 þ Treg as well as gd-TCR Treg cells in prostate and breast cancer Peng et al, 2007). The former cells expressed Foxp3 molecules, while the latter did not.…”
Section: Th17 Cellsmentioning
confidence: 93%
“…Thus, the balance between murine Treg cell-suppressive function and naive/effector T-cell proliferation is controlled by TLRs through directly acting on Treg and effector T cells and indirectly acting on DCs (Figure 2). Peng et al, 2007), and showed that they also express a low level of human TLR8 molecules. One of the important questions is whether TLR8 ligands including Poly-G3 and ssRNA40 can reverse the suppressive function of CD8 þ Treg cells and gd-TCR Treg cells.…”
Section: Functional Control Of Treg Cell Function By Tlr Signalingmentioning
confidence: 99%
“…Once activated, Vd1 + T cells can drive DC maturation [215] but also kill DCs [216]. In addition, Vd1 + T cells can display properties of regulatory T cells and suppress immune responses through contact or cytokine dependent interactions [217][218][219][220], including the suppression of DC maturation in breast cancer [221,222]. Thus, it appears that the Vd1 + , Vd2 + and Vd3 + subsets of cd T cells as well as iNKT cells all play roles in the induction, polarization and/or regulation of adaptive immune responses in humans.…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%